SISTEM FILTERING DATA MAHASISWA MENGGUNAKAN FRAMEWORK LARAVEL DAN LIBRARY LARAVEL EXCEL - Adriansa Wahyu Pramudita; Ramos Somya (Teknik Informatika, 2021)
As Lembaga Penjamin Mutu (LPM) or Quality Assurance Institution of Universitas Kristen Satya Wacana (UKSW), it has many responsibilities to improve quality of UKSW such as the quality of curriculum, lecturers, facilities, etc. LPM works with big data on daily basis, therefore it needs to improve efficiency at work and of course to make it easier. In this case LPM often have to deal with Pangkalan Data Pendidikan Tinggi (PDDikti) to give report to the government about student data of UKSW. Therefore, it is needed a web-based system to filter active student from excel file so that it will make LPM works easier and more efficient.